PENATALAKSANAAN FISIOTERAPI PADA KASUS FROZEN SHOULDER E.C CAPSULITIS ADHESIVA SINISTRA DI RST. dr. SOEDJONO MAGELANG - Sofianata, Agung; , Arif Pristianto, SSt.FT.,M.Fis (2016)
ABSTRACT MANAGEMENT PHYSIOTHERAPY IN THE CASE OF FROZEND SHOULDER E.C CAPSULITIS ADHESIVA SINISTRA IN RST. dr. SOEDJONO MAGELANG (Agung Sofianata, 2013, 55 pages) Background: Frozen Shoulder is a symptom that can cause a damage in shoulder area that can cause pain and limited range of motion. In this case can be treat with physiotherapy modalities . Physiotherapy in this case can reduce pain and enhance the range of motion with micro wave diathermy, manipulation therapy, and exercise therapy. Purpose: To know the physiotherapy intervention to reduce pain, and enhance functional activity in case of frozen shoulder e.c capsulitis adhesive case using physiotherapy modalities which are micro-wave diathermy, manipulation therapy, and exercise therapy. Results: After 6 times treatment, the results obtained ratings of painful silence T1: 2, to T6: 1, tenderness T1: 3, to T6: 2, painful motion of active T1: 4, to T6: 2, pain motion passive T1: 5, to T6: 3, enhance range of motion S: T1: 30-0-100, to T6: 45-0-115, F: T1: 65-0-15, to T6: 80-0-30, R(F=65): T1: 55-0-70, to T6: 70-0-80, T: T1: 10-0-110, to T6: 20-0-120, inability functional activities T1: 44,28%, to T6: 35.71%. Conclusion: Micro wave diathermy can reduce pain in Frozen Shoulder e.c capsulitis adhesive on the left shoulder, manipulation therapy can enhance range of motion in Frozen Shoulder e.c capsulitis adhesive on the left shoulder, and exercise therapy can enhance functional activity in the left shoulder with frozen shoulder e.c capsulitis adhesive. Keywords: Frozen Shoulder, micro wave diathermy, manipulation therapy, and exercise therapy.